2011
DOI: 10.1016/j.canlet.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of the HDAC inhibitor vorinostat and radiation in metastatic neuroblastoma: Efficacy and underlying mechanisms

Abstract: Histone deacetylase (HDAC) inhibitors can radiosensitize cancer cells. Radiation is critical in high-risk neuroblastoma treatment, and combinations of HDAC inhibitor vorinostat and radiation are proposed for neuroblastoma trials. Therefore, we investigated radiosensitizing effects of vorinostat in neuroblastoma. Treatment of neuroblastoma cell lines decreased cell viability and resulted in additive effects with radiation. In a murine metastatic neuroblastoma in vivo model vorinostat and radiation combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 20 publications
0
63
1
Order By: Relevance
“…Increased accessibility to DNA-damaging agents, however, is unlikely to be the only mechanism responsible for the effects of treatment with HDAC inhibitors. HDACs have also been shown to regulate the transcription rate and the protein levels of several components of the DDR cascade (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Hdac Inhibitors and The Dna Damage Responsementioning
confidence: 99%
See 3 more Smart Citations
“…Increased accessibility to DNA-damaging agents, however, is unlikely to be the only mechanism responsible for the effects of treatment with HDAC inhibitors. HDACs have also been shown to regulate the transcription rate and the protein levels of several components of the DDR cascade (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Hdac Inhibitors and The Dna Damage Responsementioning
confidence: 99%
“…The combination of DNA-damaging agents with HDAC inhibitors induces a higher number and prolonged duration of phosphorylated histone H2AX (gH2AX) nuclear foci, which are classical markers of DSBs (12,17,18,21,23,26,(28)(29)(30). Vorinostat has been shown to act as a radiosensitizer of lung cancer and melanoma cells through a strong inhibitory effect on the NHEJ pathway (22,31).…”
Section: Hdac Inhibitors and The Dna Damage Responsementioning
confidence: 99%
See 2 more Smart Citations
“…HDAC inhibition leads to histone acetylation, opening of chromatin structure, and reactivation of previously silenced genes (Johnstone, 2002). In NB, HDAC inhibitors have been shown to induce apoptosis and impair VEGF production (MuhlethalerMottet et al, 2008), restore the p53 pathway (Condorelli et al, 2008), synergize with retinoic acid to inhibit growth (Coffey et al, 2001), and enhance RT (S. Mueller et al, 2011). In a phase I trial of vorinostat, one CR was observed in a NB patient receiving vorinostat in combination with 13-cis-retinoic acid (Fouladi et al, 2010).…”
Section: Vorinostatmentioning
confidence: 99%